Analisis Pergeseran Paradigma Cartesian-Newtonian dan Thomas Kuhn: Cartesian-Newtonian Paradigm Shift Analysis and Thomas Kuhn - Nurdiyanto, Nurdiyanto; Nikmah, Nurvina Laelatul; Kahfi, Al; Islam, Muhammad Thoriqul; Mushaffa, Arju (Undiksha, 2025)
This study aims to analyze the Cartesian-Newtonian paradigm and the Thomas Kuhn paradigm within the discipline of the philosophy of science, as well as to examine the paradigm shift between the two. This research employs a qualitative approach using the library research method. Data were obtained from primary sources such as journal articles, e-books, and online media, as well as secondary sources including proceedings, magazines, newspapers, and scientific websites like Scopus and Science. Data collection was conducted by classifying relevant literature and analyzing it descriptively. The study refers to several works, including Hermawan (2009) on Islamic educational philosophy, Rahmawati et al. (2024) on theory and knowledge paradigms, Salam (2014) on Mulyadhi Kartanegara’s critical thought, and Utomo (2016) on the ideal concept of progressive law. The findings show that the Cartesian-Newtonian paradigm, influenced by Rene Descartes and Isaac Newton, emphasizes ontological and epistemological assumptions about a fixed and measurable world. Meanwhile, Thomas Kuhn’s paradigm highlights the stages of scientific paradigm shifts and frames knowledge from an axiological perspective. The study concludes that paradigm shifts reflect a dynamic worldview, shaped holistically by ontological, epistemological, and axiological elements.